Evaluation of phosphate depressants in the phosphate - Zhang, P.
The use of phosphate depressants in the cationic flotation of silica from francolite in the Florida phosphate industry is rarely practiced. The occasional use of gelatinized starch derivatives and pH adjustments to assure a sligthly alkaline flotation feed slurry pH have beed used in some processing plants to improve selectivity. This paper presents a preliminary laboratory comparison of several potential phospahe depressants for use with the flotation of siliceous phospahtes. it was found that starch is ideal for floating fine (-35mesh) silica from phosphate,while sodium tripolyphosphate may be the best for coarser (+35 mesh) feeds.
Keywords: Phosphate depressant